The Impact of Experience-based Learning on Physical Readiness and Backstroke Mastery - Sanjaya, Pande Made Dharma; Priyudahari, Bhujangga Ayu Putu (LPPM Undiksha, 2022)
There are still some students who make mistakes in the backstroke swimming competition so that they are disqualified. This is the reason why this research aims to analyze experience-based learning on physical fitness and backstroke mastery. The design of this study is a quasi-experimental design in the form of a posttest control group design. The number of samples in this study was 60. The data collection process used was the test and observation method. The data analysis method of this research is descriptive analysis and inferential statistical analysis using manova. The results showed that experience-based learning affected students' physical readiness and mastery of backstroke swimming both simultaneously and partially, this was indicated by the sig. <0.05. From the descriptive data, the results were also obtained in the form of students' backstroke swimming mastery variable being more influenced by experience-based learning. This can be seen from the average difference in value, which is large compared to the physical readiness variable. So it can be recommended that experience-based learning can be used as one of the innovative learning for swimming sports.